Comparison of two methods for subpubic angle measurement from reconstructed three-dimensional pelvic model - Siti Hanum Mohd Ali; Normaliza Omar; Shafie, MS; Ismail, NAN; Hadi, H; Nor, FM (Int Assoc Law & Forensic Sciences, 2024)
Indexed by WOS/ Scopus